Serum Electrolyte Levels In Preeclamptic Women: A Comparative Study - MAGNA MANJAREEKA; SITIKANTHA NANDA (International Journal of Pharma and Bio Sciences, 2012)
One of the most complicating factors during pregnancy is preeclampsia, a hypertensive disorder leading to a variety of problems. Serum electrolyte levels and anion gap, mean weights, SBP/DBP of preeclamptic age-matched women (devoid of diabetes, UTI, renal and liver disorders) in their third trimester, as compared to their normotensive counterparts, have been measured, analysed and compared with results of earlier studies. The preeclamptic group exhibits significant lowering of serum Ca2+ (-22.6 %) or K+ (- 3.85 %) and significant enhancement of each of serum Na+ (+ 6.93 %), Cl- (+ 7.25 %), HCO3- (+ 8.74 %) and an insignificant and small increase in anion gap (+ 1.5 %). The observed results do not show any region-specific changes. Most plausible explanations are offered for the observed results.